Real-world assessment of sparsentan’s drug safety framework - Fu, Wenjing; Wang, Jingyu; Xue, Yuzhou; Pan, Dikang (Renal failure, 2025)
Sparsentan has been approved for reducing proteinuria in adult patients with primary IgA nephropathy (IgAN) at risk of rapid disease progression, yet comprehensive studies evaluating its drug safety framework are lacking. Adverse event (AE) reports following the market release of sparsentan were collected from the U.S. Food and Drug Administration AE Reporting System. Disproportionate analysis was used to identify previously unrecognized positive novel signals at both the system organ class and preferred term levels. Additionally, analysis on clinical priorities and subgroup analysis were conducted. A total of 504 patients with IgAN were included. Two novel system organ classes and 14 novel preferred terms were identified. Hypotension and dizziness were established as moderate clinical priority events. Males had a higher relative risk of nausea, peripheral edema, feeling abnormal, decreased blood pressure, and hypotension, while females were at greater risk for fatigue, pain, increased blood creatinine, dizziness, and somnolence. Among those aged 18-45, the relative risk of experiencing fatigue, pain, and dizziness was higher, individuals aged 45 and older had a higher relative risk of peripheral edema, decreased blood pressure, and hypotension. Based on the available AE reporting data, sparsentan exhibits a favorable safety profile, with no high-priority clinical events identified. Our findings offer valuable insights to optimize the use of sparsentan and understand its potential side effects.